Meditation as Source of Higher States of Consciousness: Mind and Body Healing - Made Jessita Kirandra (Fakultas Ilmu Pendidikan)
The practice of meditation has been recognized for more than 5,000 years and raised interest in many scientific fields. Yet, meditation is often misconstrued as an activity to empty the entire contents of one’s mind. Whereas, in the contradictory fact, studies have shown how meditation helps individuals get acquainted with higher and deeper levels of consciousness through reportedly positive activities on brain. Furthermore, findings also identify meditation as an effective approach to mind-body intervention. This paper is a review on the comprehensive understanding of meditation and how it engages with a phenomenon where the mind and body is seen from a unified perspective, also in the sub-topic will be discussed how artificial intelligence contributes as a convenient tool to facilitate mind-body healing practice through meditation. Findings may help to introduce the general overview of meditation practices that can be adopted to improve mental health in the midst of this digital era.